Post-stroke Delivery of Valproic Acid Promotes Functional Recovery and Differentially Modifies Responses of Peri-Infarct Microglia - Kuo, Tung-Tai; Wang, Vicki; Wu, Jui-Sheng; Chen, Yuan-Hao; Tseng, Kuan-Yin (Frontiers in Molecular Neuroscience, 2021)
The specific role of peri-infarct microglia and the timing of its morphological changes following ischemic stroke are not well understood. Valproic acid (VPA) can protect against ischemic damage and promote recovery. In this study, we first determined whether a single dose of VPA after stroke could decrease infarction area or improve functional recovery. Next, we investigated the number and morphological characteristic of peri-infarct microglia at different time points and elucidated the mechanism of microglial response by VPA treatment. Male Sprague-Dawley rats were subjected to distal middle cerebral artery occlusion (dMCAo) for 90 min, followed by reperfusion. Some received a single injection of VPA (200 mg/kg) 90 min after the induction of ischemia, while vehicle-treated animals underwent the same procedure with physiological saline. Infarction volume was calculated at 48 h after reperfusion, and neurological symptoms were evaluated. VPA didn’t significantly reduce infarct volume but did ameliorate neurological deficit at least partially compared with vehicle. Meanwhile, VPA reduced dMCAo-induced elevation of IL-6 at 24 h post-stroke and significantly decreased the number of CD11b-positive microglia within peri-infarct cortex at 7 days. Morphological analysis revealed that VPA therapy leads to higher fractal dimensions, smaller soma size and lower circularity index of CD11b-positive cells within peri-infarct cortex at both 2 and 7 days, suggesting that VPA has core effects on microglial morphology. The modulation of microglia morphology caused by VPA might involve HDAC inhibition-mediated suppression of galectin-3 production. Furthermore, qPCR analysis of CD11b-positive cells at 3 days post-stroke suggested that VPA could partially enhance M2 subset polarization of microglia in peri-infarct cortex. Analysis of VPA-induced changes to gene expressions at 3 days post-stroke implies that these alternations of the biomarkers and microglial responses are implicated in the upregulation of wound healing, collagen trimmer, and extracellular matrix genes within peri-infarct cortex. Our results are the first to show that a low dose of VPA promotes short-term functional recovery but does not alter infarct volume. The decreases in the expression of both IL-6 and galectin-3 might influence the morphological characteristics and transcriptional profiles of microglia and extracellular matrix remodeling, which could contribute to the improved recovery.